Neurogenic differentiation potential of human nasal mucosa obtained from the middle and inferior turbinates - Tan, Shi Nee; Yogeswaran Lokanathan,; Rohaina Che Man,; Aminuddin Saim,; Ruszymah Hj Idrus, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Olfactory bulb and nasal mucosa are one of the sources for neural stem cell, including the superior and middle turbinates (MT). The middle and inferior turbinates (IT) provides the largest area of nasal mucosa which is technically easier to harvest the stem cell for future transplantation. The ability of nasal respiratory epithelial cells (RECs) and nasal fibroblasts (NFs) from both middle and inferior turbinates to differentiate into neural lineage (NL) cells were compared in this study. Six redundant human MT and IT from post-sinus surgery were digested and cultured. The RECs and NFs were separated and induced with neurotrophic factors of forskolin, human basic fibroblast growth factor (bFGF), platelet-derived growth factor-AA (PDGF-AA) and heregulin-β1-EGF-domain. Based on immunocytochemistry and quantitative PCR, the NL induced NFs of MT expressed GFAP, Nestin and P75 receptor. NL induced RECs from MT and IT expressed GFAP and Nestin but did not express the P75 receptor protein. Regarding the control, the non-induced RECs and fibroblasts expressed Nestin only. This study demonstrated that nasal mucosa cells from both IT and MT have the potential to differentiate into neural lineage cells even though the fibroblasts of MT are superior in term of quality. Hopefully, these tissues will provide better donor area with less morbidity for autologous or allograft transplantation in future neural regenerative medicine.